Exploring and comparing renal adverse effects between PARP inhibitors based on a real-world analysis of post-marketing surveillance data - Xu, Qiuyu; Jiang, Lin; Chen, Gang; Ai, Sanxi; Fan, Xiaohong; Wang, Gangan; Jia, Chunyu; Wang, Jiahui; Zheng, Ke; Zhao, Bin; Qin, Yan; Li, Xuemei (Frontiers in Medicine, 2024)
Poly (ADP-ribose) polymerase inhibitors (PARPis) are emerging targeted therapeutic agents in oncology, primarily indicated for ovarian and metastatic breast cancer. Acute kidney injury (AKI) has been observed in patients undergoing PARPi treatment, while there is still a lack of comprehensive comparisons of AKI associated with different PARPis. Our study aimed to extensively characterize the renal adverse effects (RAEs) of PARPi using real-world data.Disproportionality analysis and Bayesian analysis were employed for data mining to identify suspected RAE cases after different PARPis use within the Food and Drug Administration's Adverse Event Reporting System from January 2004 to September 2023. The time to onset, fatality, and hospitalization rates of PARPi-related RAEs were also investigated.We identified 1,696 PARPi-related RAEs, predominantly affecting patients over 85 (56.31%). Veliparib exhibited a more pronounced association with renal adverse effects compared to others, as indicated by the highest reporting odds ratio (ROR=29.20, 95%CI=8.79-96.97), proportional reporting ratio (PRR=19.80, χ2=72.62), and empirical Bayes geometric mean (EBGM=19.80, the lower 90% one-sided CI=7.25). The median time to RAEs onset was 15 (IQR 6-55.75) days following the initiation of PARPi therapy. PARPirelated RAEs generally led to a 28.15% hospitalization rate and a 4.34% fatality rate.Although the majority present with reversible creatinine elevation, PARPi-related RAEs merits broader attention, given its potential for clinical consequences. We should strive to early identify those individuals who may have irreversible kidney damage. The focus should be directed toward monitoring renal function in individuals receiving PARPi, especially in senile people and those with a predisposition to AKI.